KEPATUHAN PENGGUNAAN OBAT PADA PASIEN HIPERTENSI DI INSTALASI RAWAT JALAN SALAH SATU RSUD DI WILAYAH DAERAH ISTIMEWA YOGYAKARTA - Muhammad Muhlis; Alissa Jihan Prameswari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
The study aimed to determine the description of compliance with drug use and the relationship between distance of health services, duration of illness, and other illnesses to compliance with drug use in outpatient hypertension patients in the period January-February 2019 in One Hospital in the Special Region of Yogyakarta. This study was an observational study with a cross sectional design. Sampling using a questionnaire using accidental sampling technique as many as 96 patients. Compliance was analyzed using Univariate and Bivariate analysis with the chi square method. The results showed that there were 78 patients in the obedient category (81.3%). Chi square test obtained distance of health service p = 0.462; OR = 1,690 (0,6024,741) and the presence of other diseases p = 0,818; OR = 1,294 (0,464-3,613) there is no significant relationship with compliance; long suffering from hypertension there was a significant relationship with compliance p = 0.005; OR = 6.471 (1,732-24,171). Conclusion, hypertension patients are categorized as obedient 81.3% and there is no significant relationship between distance of health services and other diseases with adherence. But there is a significant relationship between the duration of suffering from hypertension and compliance